2012
DOI: 10.1158/0008-5472.sabcs12-p5-18-13
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-18-13: Inhibiting telomerase to reverse trastuzumab (T) resistance in HER2+ breast cancer

Abstract: Background: Preclinical studies have shown the combination of imetelstat (GRN163L), an inhibitor of telomerase, and T results in synergistic growth inhibition and restoration of T sensitivity in T-resistant cells (Clin Can Res 12(10):3184–92, 2006). Here we translate those findings to the clinic with the first-in-man phase I trial of imetelstat+ T in patients (pts) with T-refractory HER2+ metastatic disease. Methods: T (6 mg/kg q3 wk) was administered with increasing doses of imetelstat (240/300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Telomerase inhibitors have shown synergy with trastuzumab in inhibiting HER2-positive cancer cell growth and restoring trastuzumab sensitivity in trastuzumab-resistant cell lines [100]. Preliminary results with imetelstat (GRN163L; Geron Corporation, Menlo Park, CA, http://www.geron.com) and trastuzumab in women with trastuzumab-resistant breast cancer showed no significant toxicity, although no responses were seen [101].…”
Section: Other Targetsmentioning
confidence: 99%
“…Telomerase inhibitors have shown synergy with trastuzumab in inhibiting HER2-positive cancer cell growth and restoring trastuzumab sensitivity in trastuzumab-resistant cell lines [100]. Preliminary results with imetelstat (GRN163L; Geron Corporation, Menlo Park, CA, http://www.geron.com) and trastuzumab in women with trastuzumab-resistant breast cancer showed no significant toxicity, although no responses were seen [101].…”
Section: Other Targetsmentioning
confidence: 99%
“…A phase 1 study of imetelstat in patients with trastuzumab-resistant breast cancer has been completed, and, in an initial report of 10 patients with trastuzumab-refractory HER2 + metastatic breast cancer enrolled in the study, no objective responses were reported; however, two patients achieved stable disease (ClinicalTrials.gov identifier NCT01265927). 95 VEGF inhibitors. HER2 induction of VEGF expression is believed to play a role in the pathogenesis of HER2amplified breast cancer.…”
Section: Investigational Options For Her2 + Therapy-resistant Breast mentioning
confidence: 99%